Da’wah Communication on the Musawarah YouTube Channel (Perspective of Shafwatut Tafasir Interpretation) - Salsabyla Nuril Ula; Singgih Muflihhafiz Labibah; Moh. Ali Aziz (Kalijaga Journal of Communication, 2026)
Digital da'wah often faces challenges in maintaining emotional depth and theological groundedness amidst the fast-paced nature of social media. This study addresses the need for a da'wah model that balances contemporary communication styles with classical Islamic interpretation. This study analyzes the communication strategy of da'wah through a presentation of the issue's background in the Musawarah Podcast episode “Kekuatan Itu Menjadikan Kita Selalu Bersama” (Strength Keeps Us Together). Using a descriptive qualitative approach with Klaus Krippendorff's content analysis, this study examines Aristotle's rhetorical elements of ethos, pathos, and logos, then integrates them with Shafwatut Tafasir's interpretation of QS—Muhammad verse 19. The results show that presenting the background of the issue plays an important role in building the moral credibility of the source (ethos), evoking emotional resonance (pathos), and strengthening the argumentation of Islamic values through life experiences (logos). Theoretically, this study contributes an integrative framework between Western rhetoric and classical Tafsir, and, practically, provides a narrative-spiritual model for digital preachers to reach urban Muslim audiences more effectively.